Evaluation of a dementia awareness programme in UK schools: a qualitative study. (August 2020) - Farina, N.; Hughes, L.J.; Jones, E.; Parveen, S.; Griffiths, A.W.; Galvin, K.; Banerjee, S.
Abstract: Objectives: 'Dementia Friends' is a programme used to raise awareness of dementia, developed by the Alzheimer's Society, which has been delivered across the UK to diverse populations, including adolescents. However, there is little evidence available with regards to adolescents' perceptions of the programme and its impact. This study aims to explore this in a group of adolescents from the south of England. Study design: Focus group discussions. Methods: Thirty adolescents aged between 11 and 16 years were recruited from two schools in East Sussex, England. All had participated in a Dementia Friends session in the past month. Focus group discussions were transcribed, coded and themes were created using inductive thematic analysis. Results: Four themes were identified: (1) perceptions and experiences of dementia, (2) outcomes and learning from Dementia Friends session, (3) reactions to the Dementia Friends session and (4) identified future learning needs. Conclusions: Adolescents had generally positive opinions about Dementia Friends, particularly the interactive nature of the session. Whilst they felt participating in Dementia Friends improved their attitudes and knowledge, they were often left wanting to learn more. Future research needs to empirically evaluate the extent to which Dementia Friends may improve attitudes and knowledge of dementia. Highlights: Dementia Friends is an enjoyable initiative for adolescents. Adolescents held positive attitudes and perceptions about people with dementia. Adolescents felt the initiative improved their knowledge about dementia. Future research needs to quantify the initiatives impact on attitudes and knowledge.